Nutrient management for cutting production in carnation (Dianthus caryophyllus) - MOMIN, KALKAME CH; DHIMAN, S R; GUPTA, Y C; BHARADWAJ, S K; KUMAR, SUNIL (The Indian Journal of Agricultural Sciences, 2015)
An experiment was conducted to study the effect of nutrient management on cutting production of carnation (Dianthus caryophyllus L.). The experiment consisted of five fertilizer modules with four cultivars and it was laid out in factorial randomized block design with three replications. Findings of the experiment revealed that fertilizer module FM5 comprising of 20-5-5 g/m2 NPK as basal application along with 200 ppm N + 280 ppm K as fertigation given twice a week resulted in the production of cuttings with maximum stem diameter (0.75 cm), weight of cutting (5.22 g), number of cuttings/plant/harvest (4.25), total number of cuttings (16.98) and yield of cuttings/square metre (152.78). Amongst the cultivars, Madras exhibited the maximum stem diameter (0.82 cm), weight of cutting (4.60 g), number of cuttings/plant/harvest (3.80), total number of cuttings/plant (15.12) and yield of cuttings/square metre (152.78), while, cultivar White Wedding recorded minimum stem diameter. Interaction effect revealed that module FM5 wasfound to be best in getting good quality cuttings in cultivars Farida, Niva and Madras which gave the maximum number of cuttings/plant/harvest, total number of cuttings/plant, yield of cuttings/metre square and weight of the unrooted cuttings. In cultivar White Wedding, fertilizer modules FM4 consisting of 20-15-10 g/m2 NPK (as basal) along with 175 ppm N and 245 ppm K (fertigation twice a week) gave the best quality cuttings. The time taken for first and successive harvesting of cuttings varied with the season with minimum days during summer and maximum days during winter.